A complementarity-based equilibrium model of biodiesel market, in Thailand - Somkiat Khwanpruk; Chalida U-tapao (My University, 2018)
This paper presents a complementarity-based model making a decision for energy production in biodiesel market. This model has three strategic players complete against each other on the biodiesel productions. All three players make up biodiesel from agricultural products and they are price-takers. The first player represents producers who produce and sell biodiesel from palm oil. The second and third players produce and sell biodiesel from coconut oil and soybean oil, respectively. The strategic player’s decisions involve quantities of palm, coconut and soybean oil related with the market price. This paper uses operation research to optimize a decision maker’s objectives within the limits of available agricultural products and also provide results for sustainable energy production.
Keywords: Complementarity (molecular biology); Soybean oil; Agribusiness; Oil Palm Production and Sustainability